Analysis Numeracy Literacy Skills of High School Students in Biodiversity Material Based on Minimum Competency Assessment Questions - Aini, V.; Hidayat, T.; Kusnadi, K.; Williams, C.; Hadibarata, T. (Jurnal Pendidikan IPA Indonesia, 2024)
Proficiency in numeracy literacy is indispensable for contemporary individuals, including comprehension of numbers, symbols, and analysis of quantitative data such as graphs, tables, and charts. In this context, students can effectively apply knowledge in practical real-world scenarios with robust numeracy literacy skills. The urgency of numeracy literacy skills needs to be increased by providing a training process through numeracy questions in various subjects including biology. Therefore, this research aimed to analyze numeracy literacy skills of high school students in Biology on biodiversity material adapted to the Minimum Competency Assessment questions using a descriptive and qualitative approach. A convenience sampling technique was used to obtain 80 students from Grade 10 of SHS IT Insan Mulia in Pringsewu, Lampung, Indonesia. The research instrument consisted of 11 multiple-choice Minimum Competency Assessment questions which included numeracy literacy indicators. The result showed that students' numeracy literacy skills were not satisfactory, consisting of 55.3%,54.4%, and 39.4% on content, cognitive processes, and context, respectively. The analysis reported students’ need for practice and improvement in the context dimension.